PRE-EXERCISE ARGININE SUPPLEMENTATION INCREASES TIME TO EXHAUSTION IN ELITE MALE WRESTLERS - Yavuz, H.U.; Turnagol, H.; Demirel, A.H. (Biology of Sport, 2014)
Dietary supplements containing arginine are among the most popular ergogenics intended to enhance strength, power and muscle recovery associated with both anaerobic and aerobic exercise. The aim of the present study was to evaluate the possible effect of pre-exercise acute intake of arginine on performance and exercise metabolism during incremental exhaustive exercise in elite male wrestlers. Nine volunteer elite male wrestlers (24.7±3.8 years) participated in this study. The test-retest protocol was used on the same subjects. The study was conducted using a cross-over design. A single dose of arginine (1.5 g · 10 kg-1 body weight) or placebo was given to the subjects after 12 hours fasting (during the night) for both test and retest. Subjects were allowed to drink water but not allowed to eat anything between arginine or placebo ingestion and the exercise protocol. An incremental exercise protocol was applied and oxygen consumption was measured during the exercise. Heart rate and plasma lactate levels were measured during the exercise and recovery. Results showed that in the same working loads there was no significant difference for the mean lactate levels and no difference in maximum oxygen consumption (arginine 52.47±4.01 mL · kg-1 · min-1, placebo 52.07±5.21 mL · kg-1 · min-1) or in maximum heart rates (arginine 181.09±13.57 bpm, placebo 185.89±7.38 bpm) between arginine and placebo trials. Time to exhaustion was longer with arginine supplementation (1386.8±69.8 s) compared to placebo (1313±90.8 s) (p<0.05). These results suggest that L-arginine supplementation can have beneficial effects on exercise performance in elite male wrestlers but cannot explain the metabolic pathways which are responsible from these effects.